Collaboration Anxiety: What Do We Do About It? - Lynette Harper; Marina Niks; Allison Tom (Adult Education Research Conference, 2000)
The growing momentum of collaborative and participatory research initiatives is raising new issues in social science research. Collaborative research projects differ dramatically in their theoretical and methodological approaches, but they all involve personal risk-taking by the researchers as well as the researched. We believe that the most critical topic in collaboration is the commitment to changing the power dynamics in a research relationship.